2018
DOI: 10.1055/a-0578-8689
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antibody-Based Enzyme-Linked Immunosorbent Assay for Determination of Homoharringtonine

Abstract: Homoharringtonine (HHT), also known as omacetaxine, is a natural compound found in the genus and is a promising pharmaceutical drug used for the treatment of chronic or accelerated phase chronic myeloid leukemia. As a tool for the quantitative determination of HHT, a specific monoclonal antibody against HHT (MAb 6A1) was generated by conjugates prepared via sodium periodate-mediated oxidation. The developed indirect competitive enzyme-linked immunosorbent assay (icELISA) using MAb 6A1 was found to be highly sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Considering our recent reports about specic MAbs prepared using BSA conjugates containing only two target molecules, [20][21][22] very low hapten numbers may be sufficient for producing highly specic antibodies although some study concluded between 8 and 25 hapten number were optimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering our recent reports about specic MAbs prepared using BSA conjugates containing only two target molecules, [20][21][22] very low hapten numbers may be sufficient for producing highly specic antibodies although some study concluded between 8 and 25 hapten number were optimal.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40 years ago, the appropriate hapten numbers had already been investigated by Erlanger for the production of antihapten antibodies using BSA conjugates and he concluded that between 8 and 25 molecules were optimal. 19 However, in our recent reports, highly specic and highly sensitive antibodies were successfully produced against harringtonine, 20 homoharringtonine, 21 and monocrotaline, 22 despite only having hapten numbers of 2 per BSA molecule. Thus, AG-BSA conjugates obtained herein were used as immunogens for further antibody production.…”
Section: Determination Of Hapten Numbers By Maldi-tof-msmentioning
confidence: 99%